Genetic diversity and fitness in small populations of partially asexual, self-incompatible plants - Navascués, Miguel (Nature Publishing Group, 2010)
How self-incompatibility systems are maintained in plant populations is still a debated issue. Theoretical models predict that self-incompatibility systems break down according to the intensity of inbreeding depression and number of S-alleles. Other studies have explored the role of asexual reproduction in the maintenance of self-incompatibility. However, the population genetics of partially asexual, self-incompatible populations are poorly understood and previous studies have failed to consider all possible effects of asexual reproduction or could only speculate on those effects. In the present study, we investigated how partial asexuality may affect genetic diversity at the S-locus and fitness in small self-incompatible populations. A genetic model including an S-locus and a viability locus was developed to perform forward simulations of the evolution of populations of various sizes. Drift combined with partial asexuality produced a decrease in the number of alleles at the S-locus. In addition, an excess of heterozygotes was present in the population, causing an increase in mutation load. This heterozygote excess was enhanced by the self-incompatibility system in small populations. In addition, in highly asexual populations, individuals produced asexually had some fitness advantages over individuals produced sexually (due to the increased heterozygosity, sex produces the homozygosis of deleterious alleles). Our results suggest that future research on the role of asexuality for the maintenance of self-incompatibility will need to (1) account for whole genome fitness (mutation load generated by asexuality, self-incompatibility and drift) and (2) acknowledge that the maintenance of self-incompatibility may not be independent of the maintenance of sex itself.